PROBLEM BASED LEARNING FOR EPISTEMOLOGICAL COMPETENCE: THE KNOWLEDGE ACQUISITION PERSPECTIVES - Masek, Alias; Yamin, Sulaiman (Journal of Technical Education and Training, 2011)
This article explores the potential of Problem Based Learning (PBL) for epistemological competence in< an engineering education area. The main idea is to explore how the processes in PBL promote knowledge acquisition that lead to an individual deep content learning. A review has been done from theoretical and conceptual aspect, as well as supportive evidence from several empirical findings. Within this, knowledge is constructed from the basic knowledge of concepts, principles, and procedural knowledge with integration to previous knowledge and experiences. The concepts and principles are linked and integrated with each other, forming a procedural knowledge, which promotes deep content learning. However, supportive evidence from the recent research literature indicates inconclusive findings, which called for more studies to provide more empirical evidence to investigate the effectiveness of PBL on knowledge acquisitions.